Craniomandibular Osteopathy in a Bitch - Leite Rodrigues, Camila; Peres Pereira, Guilherme; Fujimura, Mariana Mika; Mara Lopes, Danielle; de Lima Grapiglia, Anaísa; dos Santos, Fábio Guilherme; Dall’Agnol Gianezini, Estela; Kanashiro Oyafuso, Mônica (Acta Scientiae Veterinariae, 2025)
Background: Craniomandibular osteopathy (CMO) is a self-limiting condition that causes bone proliferation predominantly, mainly affecting tympanic bullae, branches of the jaws and temporomandibular joints. The disease appears to most commonly affect specific dog breeds between 3 and 8 months of age, with Terrier breeds being predisposed due to potential recessive genetic factors. While its exact etiology remains elusive, associations with viral or bacterial infections have been documented in other breeds. Clinical manifestations typically include pain, fever, facial edema, dysphagia, anorexia, dehydration, excessive salivation, and weight loss. Diagnosis relies on clinical signs, radiographic imaging, and histological examination, with visualization of generalized thickening of the bone trabeculae. Pain control is crucial to improving the prognosis of the disease, and usually involves anti-inflammatory and/or opioid medications for pain control, alongside nutritional support. Prognosis varies widely, with euthanasia being a consideration in severe cases. This paper aims to present a detailed clinical case of craniomandibular osteopathy in an American Bully dog, outlining its clinical evolution, diagnostic findings, therapeutic interventions, and the longitudinal monitoring of clinical, radiographic and laboratory parameters over approximately 1 year. Case: This case involved a 3-month-old American Bully bitch exhibiting signs of lethargy, dysphagia, anorexia, excessive salivation, and intense craniofacial pain. Physical examination revealed mandibular and frontal swelling, tenderness, dehydration, and fever, along with abnormal pulmonary auscultation findings (respiratory stridor). Laboratory tests and imaging diagnosis were requested to clarify the diagnosis. Laboratorial analyses indicated mild anemia, thrombocytosis, leukocytosis, elevated alkaline phosphatase, and hyperphosphatemia. Cranial radiography confirmed typical craniomandibular osteopathy features (palisade periosteal reaction and increased radiopacity of the mandible and thickening of the skull bones). Following hospitalization for pain management, the patient exhibited significant improvement post-analgesic treatment with methadone and was discharged with pain relief medication based on opioid and non-steroidal anti-inflammatory drugs. Subsequent follow-up revealed a reduction in clinical signs, with adjunctive strategies such as acupuncture and oral gabapentin administration proving beneficial. Sterilization surgery was performed, followed by gradual medication tapering. A radiographic assessment 3-month post-surgery demonstrated marked improvement in craniomandibular osteopathy associated changes. Discussion: Craniomandibular osteopathy presents a significant clinical challenge in affected dogs, characterized by debilitating pain and associated clinical signs. Cranial radiography serves as a cornerstone in diagnosis, guiding therapeutic interventions. While traditional analgesics like Tramadol hydrochloride and Carprofen may exhibit limited efficacy, Gabapentin emerged as an effective alternative in pain management. Complementary modalities such as acupuncture complemented conventional therapy, enhancing analgesic effects. Sterilization appeared to confer additional clinical benefits, with follow-up radiographs indicating favorable disease progression. This case underscores the importance of a multimodal therapeutic approach and longitudinal monitoring in managing CMO, offering insights into optimizing patient care and prognostication. Keywords: canine, gabapentin, hyperostosis, osteopathy, skull. Título: Osteopatia craniomandibular em uma cadela Descritores: canino, gabapentina, hiperostose, osteopatia, crânio.